2017
DOI: 10.1007/s00420-017-1206-2
|View full text |Cite
|
Sign up to set email alerts
|

Smoking modify the effects of polycyclic aromatic hydrocarbons exposure on oxidative damage to DNA in coke oven workers

Abstract: Our findings quantitatively demonstrate that workers exposed to coke oven fumes and smoking will cause more serious DNA oxidative damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Our study revealed smoking and 1-OHP co-exposure was positively related to high 8-OHdG levels, indicating smokers, which are occupational exposed to PAH in the long term, may have more serious oxidative damage to DNA. These results were consistent with the previously reported findings [15].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study revealed smoking and 1-OHP co-exposure was positively related to high 8-OHdG levels, indicating smokers, which are occupational exposed to PAH in the long term, may have more serious oxidative damage to DNA. These results were consistent with the previously reported findings [15].…”
Section: Discussionsupporting
confidence: 94%
“…Smoking has a strong effect on oxidative DNA damage, and PAH exposure is also related to oxidative DNA damage among occupational workers and general population [1114]. There is a dose-dependent relationship of smoking and PAH metabolites in the risk of oxidative damage to DNA [15]. However, a challenge remains to fully understand the molecular mechanism of lifestyle - environmental factors between smoking and occupational PAH co-exposure effect on oxidative DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, multiple urine sample measurements should be used in future studies to evaluate the individual long-term exposure to environmental PAH. Accumulative epidemiologic studies also use single-point urinary PAH metabolites as internal exposure biomarkers, and random single-point PAH metabolites can be used to evaluate PAH exposure levels [47, 50]. Third, none of the birth outcomes considered the population standard for expected growth, which was mainly because the features of recruited subjects were not suitable for considering the clinical relevance in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case of the fisherman of the second observation who was a smoker and exposed to diesel exhaust; a case study on lung cancer among Swedish dockworkers exposed to diesel exhaust and smoking confirmed a strong interaction between these two factors [16]. Similarly, it is well established that in workers exposed to polycyclic aromatic hydrocarbons, smoking causes more serious DNA oxidative damage than in non-exposed individuals, which may play the pivotal role in the carcinogenic mechanism of lung cancer [17].…”
Section: Discussionmentioning
confidence: 99%